Case C-368/21: A New Definition of Importation in the Sense of VAT Law? - Ojak, Sven (EC Tax Review, 2022)
Since the Eurogate II and DHL decision (CJEU, Judgment of 2 June 2016, EU:C:2016:405), it has been clear that importation in the VAT context means ‘the entry of goods into the economic network’ of the Union. However, it is problematic that neither the EU VAT Directive nor the CJEU provide a distinct definition of what is meant by this term. This article deals with the main existing theories on the interpretation of this indeterminate legal concept in the German-language literature and by the German fiscal courts. It is concluded that these theories unfortunately ignore the exposed consumption tax character of (import) VAT and therefore deliver inconsistent results in contradiction to the recent decisions of the CJEU
CRIS-Team Scopus Importer:2022-09-30
Keywords: Consumption tax; Customs; Economic cycle; Economic network; Eu vat directive; Import vat; Importation